A Hybrid Mechanism for SIP Over IPv6 Macromobility and Micromobility Management Protocols - Ong, Bi Lynn (2008)
During wireless communication between users, disconnection may occur during the handover process. The handover process causes handover latency. The high handover latency causes distortion to the wireless communication. Having understood that high handover latency causes disconnection and distortion, this research aims to reduce the handover latency. Having known that the high handover latency causes distortion to the wireless communication especially during macromobility, we propose to interwork the protocols with the aims of reducing the handover latency. SIP has been proposed to handle the macromobility management. The researchers believe that the session initiation in the application layer protocol has the possibility to reduce the handover latency. Moreover, the researchers have proposed the fast handover and hierarchical mechanisms which also have the possibilities to reduce the handover latency. The combination of fast handover and hierarchical mechanisms namely hybrid mechanism reduces the handover latency. In addition to these previous works, we propose to interwork the protocol of IPV6 mobility management, SIP and hybrid mechanism. We implement the proposed mechanism in ns-2. After the modification and implementation of these codes in ns-2, we perform the performance study of our proposed protocol. The performance study of these interworking of protocols show which of these interworking protocols work better during the mobility management of the mobile user. The performance analysis and simulation experiment show that our proposed protocol namely SIP over IPv6 macromobility management with hybrid mechanism performs better compared to the other interworking of protocols. In addition to the performance study of these interworking of protocols, we evaluate the appropriate packet size to send the data over the interworking of protocols network. The duration of handover may increase if the network is sending inappropriate packet size during data transmission. We investigate how different packet sizes affect the handover latency and throughput in these mobility managements. The simulation result shows that 512 bytes is the appropriate packet size to send data over the IPV6 mobility management mechanisms. These investigations provide information to the researchers in selecting the appropriate packet size when sending real-time multimedia applications.